Visual Communications: An Analysis of University Students' Perceptions of Rural America Based on Selected Photographs - Catherine "Dru" Glaze; Leslie Edgar; Emily Rhoades-Buck; Tracy Rutherford (Journal of Applied Communications, 2013)
Urban populations have been outgrowing rural populations since the 1920s. Studies exploring the shift in rural residents have noted items such as the job market, economy, and conveniences as factors of this change. However, few studies have been completed to examine mass media’s role in this trend. The purpose of this study was to explore college students’ perceptions about rural America, based on images selected from newspapers. This qualitative study consisted of five focus groups: two focus groups conducted at the 2009 Agricultural Communicators of Tomorrow’s (ACT) Professional Development Conference in Stillwater, Oklahoma (agricultural student focus), and three conducted at Texas A&M University (non-agricultural student focus). The focus groups followed Krueger’s (1998a, 1998b) method of questioning. Focus groups were recorded, and data was transcribed and analyzed. Common themes such as culture / values, efficiency / conservation, experience from environment, experience through observation, lack of technology, lack of accurate information, media impact / framing, occupation, proximity, relationship / ties, and stereotypes were found in both groups; however, the agricultural group indicated stronger ties to rural America. This study noted further research must be conducted to understand the total effects visual media has on rural America perceptions.
Keywords: rural America; visual communications; perceptions; college students; photographs